Pembuatan Aplikasi Sistem Pendukung Keputusan Calon Pekerja berbasis Android - Billy Abraham; Alexander Setiawan; Lily Puspa Dewi (Jurnal Infra, 2016)
Nowadays, information technology has been highly developed in various fields, one of which is in the employment field. The number of job provider applications that appear on the Android platform is still growing. For example, the famous job provider applications are jobsDB, JobStreet and LinkedIn. Companies use these applications to ease and simplify the performance of employees in the Human Resource Department. In addition, the use of these job provider applications can save paper usage and reduce cost. The downside of these job provider applications that already exist today is the absence of methods to help both sides between the company and the job seekers to take the necessary decisions. Based on these problems, then the making of a decision support system application for employment candidates) based on Android. The decision produced from AHP will be more specific and has its own weight based on the value of each criterion that are given by the company. The development of this decision support system is preceded by the design and analysis of the recruitment process by the Human Resource in PT TR, PT RM, and PT MS.The end result of the development of this system is in the form of a decision support system application for employment candidates based on Android. The development for this application is using the Ionic framework. Testing is done by asking some of the companies and prospective employee candidates to try out the application.